Transcriptional responses of Arabidopsis thaliana to chewing and sucking insect herbivores - Appel, Heidi M.; Fescemyer, Howard; Ehlting, Juergen; Weston, David; Rehrig, Erin; Joshi, Trupti; Xu, Dong; Bohlmann, Joerg; Schultz, Jack (Frontiers in Plant Science, 2014)
We tested the hypothesis that Arabidopsis can recognize and respond differentially to insect species at the transcriptional level using a genome wide microarray. Transcriptional reprogramming was characterized using co-expression analysis in damaged and undamaged leaves at two times in response to mechanical wounding and four insect species. In all, 2778 (10.6%) of annotated genes on the array were differentially expressed in at least one treatment. Responses differed mainly between aphid and caterpillar and sampling times. Responses to aphids and caterpillars shared only 10% of up-regulated and 8% of down-regulated genes. Responses to two caterpillars shared 21% and 12% of up- and down-regulated genes, whereas responses to the two aphids shared only 7% and 4% of up-regulated and down-regulated genes. Overlap in genes expressed between 6h and 24h was 3-15%, and depended on the insect species. Responses in attacked and unattacked leaves differed at 6h but converged by 24h. Genes responding to the insects are also responsive to many stressors and included primary metabolism. Aphids down-regulated amino acid catabolism; caterpillars stimulated production of amino acids involved in glucosinolate synthesis. Co-expression analysis revealed 17 response networks. Transcription factors were a major portion of differentially expressed genes throughout and responsive genes shared most of the known or postulated binding sites. However, cis-element composition of genes down regulated by the aphid M. persicae was unique, as were those of genes down-regulated by caterpillars. As many as 20 cis-elements were over-represented in one or more treatments, including some from well-characterized classes and others as yet uncharacterized. We suggest that transcriptional changes elicited by wounding and insects are heavily influenced by transcription factors and involve both enrichment of a common set of cis-elements and a unique enrichment of a few cis-elements in responding genes.